New and clean synthesis of N-substituted pyrroles under microwave irradiation - Aydogan, Feray; Basarir, Mehmet; Yolacan, Cigdem; Demir, Ayhan S. (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
N-Substituted homochiral pyrrole derivatives were synthesized by the ring-closure reaction of cis-1,4-dichloro-2-butene with various amine compounds on a silica surface under microwave irradiation. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: ALPHA-AMINO-ACIDS; HOMOCHIRAL AMINES; ALCOHOLS; DERIVATIVES; CONVERSION; PHOTOOXYGENATION; Chemistry